Laserowa korekcja krótkowzroczności i astygmatyzmu krótkowzrocznego u dzieci - Mrukwa-Kominek, Ewa; Gierek-Ciaciura, Stanisława (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Anisometropic myopia and myopic astigmatism are very often refractive error in children. Suitable correction of different vision defects in children might prevent the consequences of amblyopia and lack of development of binocular vision. This article presents the effectiveness of correction in myopia and myopic anisometropia using laser method such as PRK, LASEK and LASIK. It is the literature review.